Current timer switch in a GaAs-based nanowire coupled with polyoxometalate nanoparticle and conductive AFM tip. (6th October 2020) - Sasaki, Kentaro; Saito, Shunsuke; Kasai, Seiya
Abstract: We demonstrate a current timer switch function in a GaAs-based nanowire electrostatically coupled with a polyoxometalate nanoparticle (POM NP) and a conductive atomic force microscopy (AFM) tip. The nanowire current associated with the charge state of the POM NP on the nanowire surface abruptly changed after several ten seconds from biasing the conductive tip. The current switch timing changed depending on the tip voltage. The timer switch function appeared when the tip approached the POM NP where the AFM phase image showed phase lag at high atmospheric humidity condition. We discuss the timer mechanism in terms of the configuration of the electromechanical potential of the cantilever and dynamic potential modulation by mobile ions and polarized molecules in the water-absorbed POM NP surface.